2017
DOI: 10.1073/pnas.1619523114
|View full text |Cite
|
Sign up to set email alerts
|

Murine model indicates 22q11.2 signaling adaptor CRKL is a dosage-sensitive regulator of genitourinary development

Abstract: The spectrum of congenital anomalies affecting either the upper tract (kidneys and ureters) or lower tract (reproductive organs) of the genitourinary (GU) system are fundamentally linked by the developmental origin of multiple GU tissues, including the kidneys, gonads, and reproductive ductal systems: the intermediate mesoderm. Although ∼31% of DiGeorge/del22q11.2 syndrome patients exhibit GU defects, little focus has been placed on the molecular etiology of GU defects in this syndrome. Among del22q11.2 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…In this meta‐analysis, three of the six fetuses with 22q11.2 microdeletion presented with associated cardiac defects. Recently, a recurrent 370‐kb deletion at the 22q11.2 locus was reported to be the driver of kidney defects in both syndromic and isolated CAKUT, with the haploinsufficiency of CRKL (OMIM 602007) as the critical genetic driver . Thus, we hypothesized that the 22q11.2 deletion was the cause of CAKUT in our cases.…”
Section: Discussionmentioning
confidence: 92%
“…In this meta‐analysis, three of the six fetuses with 22q11.2 microdeletion presented with associated cardiac defects. Recently, a recurrent 370‐kb deletion at the 22q11.2 locus was reported to be the driver of kidney defects in both syndromic and isolated CAKUT, with the haploinsufficiency of CRKL (OMIM 602007) as the critical genetic driver . Thus, we hypothesized that the 22q11.2 deletion was the cause of CAKUT in our cases.…”
Section: Discussionmentioning
confidence: 92%
“…Although haploinsufficiency of TBX1 has been strongly implicated in DGS, deficiency of mouse Crkl alone also affects normal development of anterior/frontal structures, including facial features, great arteries, heart, thymus, and parathyroid, as well as posterior structures, including genitourinary (GU) tissues, as collectively manifested as a condition that resembles DiGeorge anomaly (Guris et al, 2001;Racedo et al, 2015;Haller et al, 2017;Lopez-Rivera et al, 2017). CRKL point mutations have also been identified among a large cohort of patients with renal agenesis or hypodysplasia (Lopez-Rivera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CRKL point mutations have also been identified among a large cohort of patients with renal agenesis or hypodysplasia (Lopez-Rivera et al, 2017). A distal region of the common deletion that includes CRKL has been linked to GU defects among 22q11.2DS patients, and haploinsufficiency of Crkl results in abnormal GU development in mice (Haller et al, 2017;Lopez-Rivera et al, 2017). Although CRKL coding mutations have not been linked to DGS without a 22q11 deletion, a recent study has identified non-coding mutations predicted to affect CRKL expression in the hemizygous region of the common 22q11 deletion with conotruncal defects (Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That indicates the role of genetic factors in the pathogenesis of MDAs, but the pathogenic genes are still unclear. Previous studies have found that mutations or copy number variations (CNVs) in the genes, including TBX6 , HNF1B , HOXA13 , HOXA10 , LHX1 , PBX1 , WNT9B , EMX2 , CRKL and TP63 , are associated with MDAs.…”
Section: Introductionmentioning
confidence: 99%